2023
DOI: 10.1002/gps.6044
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of neurodegeneration and neural injury as potential predictors for delirium

Tamara G. Fong,
Sarinnapha M. Vasunilashorn,
Pia Kivisäkk
et al.

Abstract: ObjectivesDetermine if biomarkers of Alzheimer's disease and neural injury may play a role in the prediction of delirium risk.MethodsIn a cohort of older adults who underwent elective surgery, delirium case‐no delirium control pairs (N = 70, or 35 matched pairs) were matched by age, sex and vascular comorbidities. Biomarkers from CSF and plasma samples collected prior to surgery, including amyloid beta (Aβ)42, Aβ40, total (t)‐Tau, phosphorylated (p)‐Tau181, neurofilament‐light (NfL), and glial fibrillary acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…After screening the titles and abstracts, 624 studies were found to be potentially eligible. Finally, 12 studies [22,24,[29][30][31][32][33][34][35][36][37][38] were selected based on the exclusion criteria (Figure 1). All reviewers agreed to include these 12 papers.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…After screening the titles and abstracts, 624 studies were found to be potentially eligible. Finally, 12 studies [22,24,[29][30][31][32][33][34][35][36][37][38] were selected based on the exclusion criteria (Figure 1). All reviewers agreed to include these 12 papers.…”
Section: Study Selectionmentioning
confidence: 99%
“…The demographic and clinical characteristics of the included studies are presented in Table 1. Nine studies [22,24,[29][30][31][32][33][34][35] involved patients with POD, three studies [36][37][38] focused on patients with POCD, and one study considered patients with pre-existing cognitive impairment [36]. CSF NfL detection was reported in six studies [24,29,[35][36][37][38], whereas four studies [24,29,35,37] discussed the correlation between CSF and blood NfL levels.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations